Investigation of Intestinal Enzyme Activity and Effects of Non-starch Polysaccharide on it - Piryaei, Masoumeh; Motamedi, Anahita; Mehrabi Far, Atefeh (International Journal of Engineering and Technology, 2018)
This experiment investigates the effects of utilizing Rahnama cultivar with high non-starchy polysaccharide content and supplementation of xylanase enzyme in poultry feed on the productivity features, nutrient digestibility and intestinal enzymes activity of 21-47 week laying hens. The experiment was conducted quite randomly and in factorial design that included eight treatments with 4 wheat levels (zero, 23, 46 and 69% that contained 1.8, 2.0, 2.2, 2.4% of xylose respectively) and two level enzymes (with and without enzyme) and 5 replications (6 hens) in each replication. During the experiment, by xylose level increase in diet, the weight (p>0.05) and mass of the egg (p>0.01) decreased and feed conversion ratio increased (p>0.05) but there was no effect on feed consumption and egg production rate. Diet supplementation with xylanase resulted in egg production increase (p>0.05), weight and mass increase of eggs (p>0.01) and improved feed conversion ratio (p>0.01). Xylose levels increase resulted in decrease in fat and metabolic energy digestibility of the diet (p>0.05); and, amylase enzymes activity in duodenum and amino peptidase, and lipase in duodenum and jejunum (p>0.01) increased. However, xylanase supplement had no effect on any intestinal enzymes. Diet supplementation with xylanase decreased viscosity of ileum (p>0.01). Increased xylanase level in diet resulted in decreased productivity features of laying hens, increased intestinal enzyme activity and decreased fat and metabolic energy digestibility.Â Â Â